Estimated prevalence rates and risk factors for common mental health problems among Syrian and Afghan refugees in Türkiye. Issue 5 (15th September 2022) - Kurt, Gulsah; Ventevogel, Peter; Ekhtiari, Maryam; Ilkkursun, Zeynep; Erşahin, Merve; Akbiyik, Nuriye; Acarturk, Ceren
Abstract : Background: Türkiye hosts 4 million refugees and asylum seekers, with Syrians and Afghans being among the largest refugee groups in country. There are limited comparative data on the conflict- and displacement-related experiences of these groups and the relation with mental health status. Aims: To assess the mental health status of Syrians and Afghans in Türkiye, identify risk factors and explore to what extent differences in mental health conditions are related to potentially traumatic events and post-displacement stressors. Method: Two parallel online survey studies were conducted between April and June 2021 among 798 Syrians and 785 Afghans in Türkiye. Data were collected on sociodemographic characteristics, traumatic events (Harvard Trauma Questionnaire), post-displacement stressors (Post-Migration Living Difficulties Checklist), symptoms of depression and anxiety (Hopkins Symptoms Checklist-25) and post-traumatic stress disorder (PTSD) (Post-Traumatic Stress Disorder Checklist for DSM-5, short form). Results: For Syrian and Afghan participants respectively, estimated prevalence rates were: 41.1% and 50.3% for depression; 39.6% and 41% for anxiety; and 41.6% and 46.5% for PTSD. In both groups, significant predictors were female gender, exposure to potentially traumatic events, and structural and socioeconomic post-displacement stressors. Additional risk factors were older age for Afghans and higher education for Syrians. Conclusions: Self-reported symptoms of common mental health problems are highly prevalent among Syrian and Afghan refugees and associated with a wide range of risk factors. After controlling for conflict- and displacement-related experiences, Afghans reported higher anxiety symptoms than Syrians, which is likely related to their legal status in Türkiye.